PERANCANGAN PENILAIAN KINERJA PEGAWAI BERBASIS WEB DENGAN METODE RATING SCALE - Siti Nurmiati (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
A company or an Employee Agency certainly needs employees to be able to carry out goals to achieve targets and perform their duties in accordance with what is desired by the leadership, but employee performance needs to be considered to know how far the ability or performance of employees in performing their duties. Employee performance is the work that has been achieved by an employee based on predetermined criteria. So that employee performance can achieve the best performance, it is necessary to assess employee performance that has been done by assessing the performance of each employee in achieving the specified work targets. After the performance appraisal is appropriate, a reward or punishment will be given to the employee concerned. In general, companies assess employee performance based solely on absenteeism, which results in employee dissatisfaction because employee performance is not included in the assessment system. The absence of an effective scheme to determine who has good employee performance because it tends to be judged by attendance. Therefore in this application will apply an employee performance appraisal which also considers other factors of the work results of employees which then from the results of the assessment will be used to give awards and sanctions based on Government Regulation 46 of 2011 by applying an assessment that is divided into two aspects include SKP (Employee Work Target) and PKP (Employee Performance Assessment).